Sociological aspects of women in primary teaching: career contexts and strategies - Evetts, Julia (1990)
This collection of articles and the book are a product of one piece of research on the careers of women in teaching. The research began with a statistical analysis of the career characteristics of women and men in teaching in one educational authority using data collated from Teachers' Service Cards. Then the research focused on women in primary teaching. Career history interviews were conducted with twenty-five married women who were headteachers of primary or infant schools from two educational areas of an English midlands county. The data for the research consisted of the Teachers' Service Cards, the interview material, together with DES official statistics on Teachers in Service. The articles appear in the order they were published. The first article contains an examination of material from the Teachers' Service Cards. Articles two, three and four are analyses of aspects of the women head teachers subjective careers based on the interview data. The fifth article examines aspects of the local labour market for primary teachers using the interview data. The sixth article argues that the use of career history material can make a significant contribution to sociological understanding about careers. The seventh article uses official statistics to explore the effects of the wider contexts of expansion and contraction on primary teachers careers. The book represents an attempt to bring together the themes and issues in the articles and to develop them further.